2012
DOI: 10.1093/carcin/bgs378
|View full text |Cite
|
Sign up to set email alerts
|

Collagen triple helix repeat containing-1 promotes pancreatic cancer progression by regulating migration and adhesion of tumor cells

Abstract: Collagen triple helix repeat containing-1 (CTHRC1) is a secreted protein involved in vascular remodeling, bone formation and developmental morphogenesis. CTHRC1 has recently been shown to be expressed in human cancers such as breast cancer and melanoma. In this study, we show that CTHRC1 is highly expressed in human pancreatic cancer tissues and plays a role in the progression and metastasis of the disease. CTHRC1 promoted primary tumor growth and metastatic spread of cancer cells to distant organs in orthotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…Previously, we showed that human OSCC specimens display aberrant amplification of the DPAGT1/canonical Wnt signaling positive feedback loop that leads to hyperglycosylation of E-cadherin and diminished intercellular adhesion (6). In this study, we have provided evidence that increased activity of this loop leads to overexpression of CTHRC1, an N-glycoprotein shown to drive tumor progression and metastasis (26). We have demonstrated that in OSCC, DPAGT1 and canonical Wnt synergize to upregulate CTHRC1 through hyperglycosylation/protein stabilization and transcriptional activation, respectively.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Previously, we showed that human OSCC specimens display aberrant amplification of the DPAGT1/canonical Wnt signaling positive feedback loop that leads to hyperglycosylation of E-cadherin and diminished intercellular adhesion (6). In this study, we have provided evidence that increased activity of this loop leads to overexpression of CTHRC1, an N-glycoprotein shown to drive tumor progression and metastasis (26). We have demonstrated that in OSCC, DPAGT1 and canonical Wnt synergize to upregulate CTHRC1 through hyperglycosylation/protein stabilization and transcriptional activation, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, Wnt/PCP signaling has been shown to drive breast cancer cell migration (37). We note that CTHRC1 can also activate other oncogenic signaling pathways, including Src/focal adhesion kinase and MEK/ERK (26). Further studies are needed to determine the details of signaling events activated by CTHRC1 in OSCC.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, it has been suggested that CTHRC1 may be largely involved in repairing damaged blood vessel tissues by limiting collagen matrix deposition and improving cell migration (Ip et al, 2011). Additionally, it been demonstrated that CTHRC1 can mediate the activities of members of the Rho GTPase family of proteins, including Rac1, RhoA, and Cdc42, which are important in regulating cell migration through their effects on cytoskeletal reorganization and cell adhesion activation (Park et al, 2013;Zhou et al, 2014). Recently, several studies have revealed that CTHRC1 is highly up-regulated in solid tumors, and may have a significant association with the pathogenic mechanisms of several human cancers, including hepatocellular carcinoma, gastric cancer, pancreatic cancer, and colorectal cancer (Kharaishvili et al, 2011;Ren et al, 2011;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%